Project Success - A Survey - Collins, A.; Baccarini, David (World Scientific Publishing, 2004)
Over the past decade there has been a growing literature on project success criteria, however there has been relatively little empirical data. This paper provides a significant contribution to the knowledge of project success by providing empirical data on the subject, by means of a survey of 150 Australian project managers on the subject of project success criteria. An analysis of the data found two distinct views: those that perceived project success solely in terms of the traditional project objectives of time, cost and quality; and those that considered success in terms of these objectives and the effectiveness of the project?s product. The traditional project management success criteria of time, cost and quality still has a strong hold within the project management community in Australia. However, the most important success criterion was considered to be the product success criterion of meeting the owner?s needs.